A Critical Short Review of Equilibrium and Kinetic Adsorption Models for VOCs Breakthrough Curves Modelling. Issue 10 (December 2015) - Valenciano, Raquel; Aylón, Elvira; Izquierdo, M. Teresa
Volatile organic compounds emission has important effects over the environment and human beings health. When these substances cannot be substituted, adsorption systems are still a very common solution to VOCs emission, but for their design, previous laboratory work is necessary: adsorption isotherms and breakthrough curves must be obtained. The first ones establish the maximal amount of adsórbate retained over the solid adsorbent for a certain pressure of the adsórbate, and the second ones define the adsorption process kinetics. Once this information is studied, a theoretical breakthrough time model can be built up, and then the scale up of the adsorption system can be developed. This process is rather complex for multicomponent gas mixtures, where a competition between adsorbates happens. Thus, the aim of this paper is to establish a guide for authors willing to develop breakthrough time prediction models for multicomponent systems through a critical review of different adsorption and kinetic models.